Prospect of Peatland Utilization For Oil Palm Plantation In Indonesia - . WAHYUNTO; AI DARIAH; DJOKO PITONO; MUHRIZAL SARWANI (Puslitbang Perkebunan, 2013)
Development of oil palm (Elaeis guenensis L.) plantations, has been proven to be able to increase people's income, and has driven the region's of economic growth in the centers of oil palm development. Utilization of peatlands for plantations will lead to high emissions of Greenhouse Gases (GHG) emissions, especially CO2 emissions. Reclamation of peatlands for palm oil plantation in order to GHG emissions can be reduced, requiring macro level of drainage network that can control water flow at the landscape level. In appropriate drainage system will accelerate the destruction of peatlands. Thus the principle of sustainable land management of oil palm plantations on peatland is needed, to minimize the impact on environmental degradation. Strategy on ground water level arrangements is necessary ie: not too shallow ground water table to support optimal growth of oil palm plantations, and also not too deep ground water level in order to the ground surface remains moist peat soil, so fire and rapid subsident in peat soil can be prevented and greenhouse gas emissions can be reduced. Key words: Estate plantation, Elaeis guenensis L., sustainable, management, peatland, water manage-ment